Pelatihan Arsip Elektronik di Era Teknologi Digital Bagi Remaja Masjid - Eni Pudjiarti; Biktra Rudianto; Siti Faizah; Verra Sofica (Indonesian Community Service Journal of Computer Science, 2024)
As an information center, each archive can help someone's memory of a particular text. As a source of documentation, archives can be used by organizational leaders in making the right decisions about the problems they face. As official proof of accountability for administration. Mosque youth are required to parade in understanding and being able to archive important documents as part of the implementation of learning. Thus the purpose of this training is to improve and make it easier for mosque youth to manage documents. To improve this it is considered important to provide workshops or training in electronic archive applications. The training was carried out using the method of providing material, practice of making electronic applications and assisting participants after completing the training activities. The results of the training illustrate that mosque youth have been able to make electronic archive applications using the application. Sebagai pusat informasi, setiap arsip bisa membantu ingatan seseorang mengenai sebuah naskah tertentu. Sebagai sumber dokumentasi, arsip dapat digunakan pemimpin organisasi dalam mengambil keputusan dengan tepat mengenai masalah yang dihadapi. Sebagai bukti resmi pertanggung jawaban penyelenggaraan administrasi. Remaja masjid dituntut untuk pawai dalam memahami dan mampu mengarsipkan dokumen-dokumen penting sebagai bagian dari pelaksanaan pembelajaran. Dengan demikian tujuan dari pelatihan ini adalah untuk meningkatkan dan mempermudah remaja masjid dalam mengelola dokumen. Untuk meningkatkan hal tersebut dianggap penting dianggap penting untuk memberikan workshop atau pelatihan dalam aplikasi arsip elektronik. Pelatihan dilaksanakan dengan metode pemberian materi, praktek pembuatan aplikasi elektronik dan pendampingan peserta setelah selesai kegiatan pelatihan. Hasil pelatihan memberikan gambaran bahwa remaja masjid telah mampu membuat aplikasi arsip elektroonik dengan menggunakan aplikasi.